Whistleblowing system and group pressure: Experimental study of fraud intention in governmental internal auditors - Hadiwidjadja, Rini Dwiyani; Muktiyanto, Ali; Perdana, Halim Dedy; Yulianto, Krist Setyo (Journal of Accounting and Investment, 2025)
Research aims: The goal of this study is to investigate the causal link between the whistleblowing system and group pressure on whistleblowing intentions.Design/Methodology/Approach: The study technique was carried out using an experimental approach utilising governmental internal auditors in Semarang City, Central Java Province, and Kupang City, East Nusa Tenggara Province, Indonesia, who served as government auditor surrogates.Research findings: The findings revealed that the whistleblowing system and group pressure impacted whistleblowers' intentions. Theoretical contribution/ Originality: The theory of planned behaviour serves as the foundation for examining individual intentions under a variety of scenarios. The independent factors in this study are whistleblowing system channels and group pressure, with whistleblowing intention serving as the dependent variable.Practitioner/Policy implication: The findings of this investigation imply that government auditors should implement a whistleblowing system capability that enhances integrity enforcement in the prevention and detection of fraud in the government sector.